PENERAPAN MEDIA PEMBELAJARAN FLASHCARD UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA MATERI CERITA FABEL KELAS 2 SD 2 MIJEN - Fara Deviana Putri; Nur Fajrie; Silvia Indriani (Jurnal Binagogik, 2025)
Reading proficiency is a fundamental skill that plays a crucial role in supporting the success of the learning process, especially at the elementary school level. Based on observations in Grade II at SD 2 Mijen, it was found that most students still faced difficulties in early reading skills, such as letter recognition, syllable blending, and accurate word pronunciation. This study aims to improve students' reading abilities through the use of flashcard learning media in fable story material. The method used is Classroom Action Research (CAR) following the Kemmis and McTaggart model, conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. Data collection techniques included observation, interviews, documentation, and learning outcome evaluations. The results showed an improvement in students’ reading skills, with an average score increase from 61 in the pre-cycle to 69 in cycle I and a significant rise to 81 in cycle II. The classical learning completeness alsoimproved from 42% (pre-cycle) to 79% (cycle II). Additionally, both student and teacher activities during the learning process improved from a fair to a good category. Flashcard media proved effective in enhancing the early reading skills of Grade II students at SD 2 Mijen, while also fostering a more enjoyable and interactive learning environment.Keywords: Early Reading, Reading Skills, Flashcards, Fable Stories